Investigate the role of individual and environmental factors in decision-making regarding normative and informational influences - Neda Ghaemi; Fatemeh Bakouie; Khatereh Borhani (پژوهش‌های علوم شناختی و رفتاری)
The current research investigated the role of individual and environmental factors in decision-making regarding normative and informational influences. The sample consisted of 50 university students (Mage= 22.5; SD= 3.5) selected using the available sampling method. An experimental task was used to evaluate the social influence on individuals' decision-making by considering two major causes of influence: normative and informational. In addition, the five personality traits questionnaire (NEO) was utilized to evaluate the role of individuals’ personalities on social influence. The T-test, the generalized linear regression model, and the Pearson correlation coefficient were used for statistical analyses. The results showed that, in general, there is no significant difference between the extent to which normative and informational influences impact individuals during decision-making. Moreover, Informational influence increases with the increasing ambiguity of decision-making conditions (p < .01). Negative opinions of others (p < .001) cause normative influence and change in people's opinions more than their positive opinions. Further, the higher the openness the lesser the extent to which people are influenced by normative factors (p = .04). It is suggested that to influence people's decisions, individual and environmental factors that affect decision-making, such as the degree of difficulty of decision-making, the feedback provided to change their opinion, and their personality, be considered.IntroductionSocial influence refers to the phenomenon in which an individual's behaviors, opinions, or beliefs change due to their interactions, often becoming similar to those of the people they interact with (Sweet & Adhikari, 2020). Social influence can cause individuals to converge their behavior and decisions toward the majority opinion of society (Oyebode & Nicholls, 2023). Conformity is a type of social influence and refers to changing one's behavior to match the responses of others (Cialdini & Goldstein, 2004). Deutsch and colleagues (1955) proposed two causes of being influenced by others: normative influence and informational influence (Deutsch & Gerard, 1955). Conformity due to informational influence occurs when an individual accepts another's viewpoint because they believe others are more knowledgeable about the situation. Conformity resulting from normative influence refers to an individual's adherence to the positive expectations of others to be liked and accepted by them (Stallen & Sanfey, 2015). In this study, in order to examine the role of individual and environmental factors affecting normative and informational influences, variables such as age and personality traits were evaluated as individual factors, and variables such as task type and conditions were considered environmental factors. MethodAn experimental method was used for the research. Fifty participants (19 female and 31 male) were selected using the convenience sampling method in the 18 to 34 age range (Mage= 22.5; SD= 3.5). Two behavioral tasks were used to evaluate normative and informational influences. The first task was to measure the informational influence, which was presented as a perceptual color identification task (Germar & Mojzisch, 2019). The second task was a judgmental task for assessing the attractiveness of paintings to measure normative influence (Liuzza et al., 2019). Revisions were the excluded measures in these tasks that were compared via t-tests.In order to evaluate the relationship between personality traits and the degree of conformity of individuals, the NEO personality questionnaire (five-factor questionnaire) was used. This questionnaire consists of 60 questions and measures five personality traits including neuroticism, openness, agreeableness, conscientiousness, and extraversion (Costa & McCrae, 2014). To evaluate the relationship between age and personality traits with the level of conformity, a generalized linear model (GLM) was used. ResultsBy analyzing both tasks, it was observed that 86 per cent of the participants revised their choice at least once according to the majority opinion. During the first task, 82 per cent of participants conformed to the majority opinion at least once, while 76 per cent did so in the second task. There was no significant difference in conformity between individuals under normative and informational influence, and people conformed to both causes in almost equal proportions.Examining the degree of conformity in the second task with independent variables showed a significant negative relationship between openness and conformity (p = 0.04, t = -2.10). Given that the second task measures normative influence, a high score of openness in a person reduces his conformity under normative influence. ConclusionThe results indicate that one factor influencing decision-making is the degree of ambiguity and difficulty of the available issue. The more ambiguous and challenging the issue, the stronger the tendency for individuals to conform to others. Another key factor is the fear of being judged; people often follow others’ choices, even in personal matters. Fear of judgment (normative influence) and the desire to make the right choice based on information (informational influence) contribute to conformity in nearly equal measure. Furthermore, the study reveals that negative preferences and judgments exert a stronger impact on conformity and response changes under normative influence than positive preferences and judgments. Regarding the influence of individual factors on conformity, the findings show that individuals who are high in openness (those who seek new experiences) are less influenced by norms. They are less concerned about others' judgments when making decisions. The implications of this study are far-reaching, particularly for individuals aiming to persuade others. Policymakers, consultants, speakers, and marketers can leverage both normative and informational influences to enhance their effectiveness in shaping opinions and decisions.